Examining the Range of Genes in Soil Microbes and Their Ability to Make Biopolymers Using RNA identification and DNA Extraction: Meneliti Kisaran Gen pada Mikroba Tanah dan Kemampuannya Membuat Biopolimer Menggunakan Identifikasi RNA dan Ekstraksi DNA - Altaee, Nadia; Aljozary, Mustafa Jasim; Hasan, Murtadha Kadhim (Universitas Muhammadiyah Sidoarjo, 2024)
This research was conducted to investigate the genetic diversity and functional capabilities of microbes in agricultural soils in Iraq. The study involved soil sampling from various agricultural farms located in the regions of Oil production station in Baghdad encompassing a range of soil types including sandy loam, clay loam, and silty clay. The research explores the genetic diversity and functional capabilities of microbes in agricultural soils, focusing on macrophages' potential to produce biopolymers through practical experiments. Diversity of the soil microbial communities was high, with an average Shannon index of 6.1. Analysis of the RNA sequencing revealed Proteobacteria (28.7%), Actinobacteria (24.5%) and Bacteroidetes (13.2%) as the main phyla and Streptomyces (9.8%), Bradyrhizobium (6.7%) and Pseudomonas (4.6%) as the most abundant genera. The most abundant functional categories in the soil microbiome as determined through metagenomic analysis were carbohydrate metabolism, amino acid metabolism and protein metabolism. Potentials of the soil, mainly of the clay loam from Basra, for PHA production were tested in biopolymer production assays, where 1.2 mg/g was produced in the clay loam from Basra. We performed differential abundance analysis and identified 500 significantly different OTUs, with Streptomyces and Bradyrhizobium as most significantly enriched, and Nitrospira and Nitrosomonas as most significantly depleted. Finally, the soil microbiome in Iraq shows a rich diversity, a high functional potential and biotechnological relevance. The study findings reveal considerable diversity and functional potential within soil microbial communities, highlighting their roles in sustainable agriculture. Understanding the genetic resources provided by soil microbes could help harness their abilities to improve crop yields while minimizing environmental impacts. Highlights: High microbial diversity in Iraqi agricultural soils, Shannon index 6.1. Abundant Proteobacteria, Actinobacteria, functional potential in metabolism, biopolymer production. Soil microbes crucial for sustainable agriculture and improved crop yields. Keywords: Soil microbiome, Metagenomics, RNA sequencing, Biopolymers, Sustainable agriculture, Poly-hydroxy-alkenoates